INDONESIAN STANDARDIZED EXAMINATION IN ISLAMIC RELIGIOUS EDUCATION - Lian G. Otaya (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2014)
This study aimed to determine the quality of Indonesian nationally standardized examination instrument (Soal Ujian Sekolah Berstandar Nasional/SUSBN) in Islamic religious education subjects (Pendidikan Agama Islam/PAI), on 2011/2012 academic year, in high school of Gorontalo City, Celebes, Indonesia. It was assessed from the aspect of qualitative analysis and quantitative analysis based on classical-modern test theory and iteman program. This is an ex post facto research. Data were collected by document analysis technique and used 215 sample from 1321 population of learners. The result shows that items of the question has a good validity level; the distribution of cognitive domain comprehenship enough; it reliability was stable; level of difficulty was categorized as fair; criteria different power are well accepted; effectiveness of detractors items are effective. However, on several points need revised in order to in line with the Regulation of the Minister of Religious Affairs and National Education Standards Agency.